Microbiome Metabolomic Analysis of the Anxiolytic Effect of Baihe Dihuang Decoction in a Rat Model of Chronic Restraint Stress - Tang L; Liu J; Yang H; Zhao HQ; Hu C; Ma SJ; Qing YH; Yang L; Zhou RR; Zhang SH (Dove Medical Press, 2024)
Lin Tang,1,* Jian Liu,2,* Hui Yang,2,* Hong-Qing Zhao,3 Chao Hu,4 Si-Jing Ma,5 Yu-Hui Qing,6 Lei Yang,1 Rong-Rong Zhou,5 Shui-Han Zhang6 1Hospital-Made Preparations Center, The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan Province, People's Republic of China; 2Medical Innovation Experiment Center, The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan Province, People's Republic of China; 3Science & Technology Innovation Center, Hunan University of Chinese Medicine, Changsha, Hunan Province, People's Republic of China; 4Department of Pharmacy, The First Hospital of Hunan University of Chinese Medicine, Changsha, Hunan Province, People's Republic of China; 5The Affiliated Hospital, Hunan Academy of Traditional Chinese Medicine, Changsha, Hunan Province, People's Republic of China; 6Institute of Chinese Medicine Resources, Hunan Academy of Chinese Medicine, Changsha, Hunan Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Rong-Rong Zhou; Shui-Han Zhang, Tel +86-0731-85920129, Email rrzhou0823@163.com; zhangshuihan0220@126.comPurpose: The Baihe Dihuang decoction (BDD) is a representative traditional Chinese medicinal formula that has been used to treat anxiety disorders for thousands of years. This study aimed to reveal mechanisms of anxiolytic effects of BDD with multidimensional omics.Methods: First, 28-day chronic restraint stress (CRS) was used to create a rat model of anxiety, and the open field test and elevated plus maze were used to assess anxiety-like behavior. Enzyme-linked immunosorbent assay (ELISA), hematoxylin-eosin staining, and immunofluorescence staining were used to evaluate inflammatory response. Besides, 16S rRNA gene sequencing assessed fecal microbiota composition and differential microbiota. Non-targeted metabolomics analysis of feces was performed to determine fecal biomarkers, and targeted metabolomics was used to observe the levels of hippocampus neurotransmitters. Finally, Pearson correlation analysis was used to examine relationships among gut microbiota, fecal metabolites, and neurotransmitters.Results: BDD significantly improved anxiety-like behaviors in CRS-induced rats and effectively ameliorated hippocampal neuronal damage and abnormal activation of hippocampal microglia. It also had a profound effect on the diversity of microbiota, as evidenced by significant changes in the abundance of 10 potential microbial biomarkers at the genus level. Additionally, BDD led to significant alterations in 18 fecal metabolites and 12 hippocampal neurotransmitters, with the majority of the metabolites implicated in amino acid metabolism pathways such as D-glutamine and D-glutamate, alanine, arginine and proline, and tryptophan metabolism. Furthermore, Pearson analysis showed a strong link among gut microbiota, metabolites, and neurotransmitters during anxiety and BDD treatment.Conclusion: BDD can effectively improve anxiety-like behaviors by regulating the gut-brain axis, including gut microbiota and metabolite modification, suppression of hippocampal neuronal inflammation, and regulation of neurotransmitters. Keywords: Baihe Dihuang decoction, 16S rRNA, metabolomics, anxiety, neurotransmitter